Strategic Implementation of Regional Food Reserves: A Case Study of Buton Regency's Food Price Control Efforts - Sinusir, Sinusir; Zeldi Putra, L.M. Ricard; Gurusi, La; Samsul, Samsul (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
This study investigates the effectiveness of Buton Regency's Regional Regulation Number 7 of 2022 on Regional Food Reserves in controlling food price volatility, a critical issue linked to Indonesia's broader food security challenges. The research focuses on two key questions: the process of distributing regional food reserves to mitigate price surges and the factors hindering the successful implementation of the regulation. Using an empirical legal research model, this study examines the functioning of law within the community, integrating primary and secondary data collected through legal document analysis, observation, and interviews with local policymakers and stakeholders. The findings reveal that, while the regulation outlines procedures for managing and distributing food reserves during price surges, these reserves have not been distributed as intended. Key barriers include the lack of supporting regulations, particularly the absence of a regent regulation to provide operational guidelines, and logistical challenges such as inadequate storage facilities. This study highlights the need for stronger regulatory frameworks and operational strategies to ensure effective implementation, contributing to the discourse on food security policy in Indonesia.